Assessment of Sustainable Building by the Participants of the Local Real Estate Market in Cze?stochowa - Sitek, Marcin (European Journal of Sustainable Development, 2017)
The inspiration for the research problem discussed in this study was sustainable investments that consist in rational and responsible construction with respect to the environment, combining economic, environmental and social aspects. The aim of the study is to find the answer to the question of whether the local market in Poland notices the benefits of sustainable building. The study proposed the hypothesis that the development of building, especially sustainable building, is a necessary component of leading the economy towards the sustainable building. A questionnaire survey was conducted among the developers to examine the status of sustainable building in local real estate market. The respondents assessed sustainable building, construction costs and limitation of risks. Furthermore, the study also used the data published by the Central Statistical Office of Poland and the Europe 2020 strategy and used the examinations of McKinsey’s survey. Analysis of the data derived from the survey revealed that the respondents perceived the sustainable building as a method to reduce costs while emphasizing lower energy consumption and the benefits of the attributes of green buildings. Furthermore, the respondents demonstrated no unequivocal evaluation of risk: answers are not consistent in terms of reduction of the risk involved in sustainable building. Keywords: sustainable building, lead markets, Europe 2020 strategy.